On the continuity of old Saami religion - Kjellström, Rolf (Scripta Instituti Donneriani Aboensis, 1987)
The purpose of my paper is to draw attention to the fact that old Saami religion is not entirely extinct. For example, sacrificial traditions, continued to live on long after the arrival of missionaries and other such activities among the Saamis. The question now is whether such sacrificing customs and similar traditions were current even later than what research has suggested and if so, how late in time. I wish to cast some light on this problem by presenting a number of examples taken in part from the literature about the Saamis, in part from personal communications from other scholars and in part from my own interviews observations in the field. What we can note is that certain traditional elements of Saami religion—at least in a few individual cases and in part perhaps in somewhat changed form—have continued to exist right up to quite recent times and, indeed, still live on, above all in the southerly parts of the region inhabited by the Lapps. In cases where the practice of making offerings ceased, the people still continued to show respect and veneration for the religious sites and could even experience something of the force emanating from them. They therefore felt a need to shield themselves from these forces and consequently followed the traditional practices. Early Saami religion and Christianity undoubtedly continued to exist side by side. It is possible that in their traditional livelihoods and even in life in general they resorted to their former well-tried religion, especially when all else failed.